Efforts to Realize Good Governance through Collaborative Governance in Sambirata Village, Cilongok District, Banyumas Regency in the Development of Cardamom Cultivation - Marfuah, Sri Rotul; Tobirin; Denok Kurniasih (Open Access Indonesia Journal of Social Sciences, 2024)
The implementation of cooperation is very influential in the progress of a village to create Good Governance. Sambirata Village, Cilongok District, Banyumas Regency, applies the principles of good governance for the development and improvement of village progress by utilizing the existing potential, namely cardamom. Cooperation has been carried out between the Sambirata Village Government and PT. Sidomuncul in 2019 – 2021. This collaboration has had a significant impact on Sambirata Village. Initially, Village-Owned Business Entities were not able to act as economic institutions in terms of capital and marketing. Apart from that, they were not able to collaborate with other agencies to help increase the buying and selling of cardamom. Now, they are starting to gradually enter and collaborate to expand marketing. However, in this case, it is still not fully developed. There is still much that has not been developed optimally, one of which is the empowerment of women farmers and also the residual value that is still left. This research aims to explain and illustrate the discourse on how to realize good governance through collaborative governance in Sambirata Village, Cilongok District, Banyumas Regency, and the development of cardamom cultivation. The method used is qualitative descriptive. The focus of this research is on efforts to realize good governance through collaborative governance in Sambirata Village, Cilongok District, Banyumas Regency, and the development of cardamom cultivation.